2015
DOI: 10.7234/composres.2015.28.5.249
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber Tow Spreading Technology and Mechanical Properties of Laminate Composites

Abstract: This paper reports a study on a method for achieving lightweight thermoplastic laminate composites referred to as tow spreading technology. Thickness of an unspread 12 K carbon fiber tow is reduced by increasing the tow width from 7 mm to 20 mm. The polypropylene (PP) film was used to stabilize and impregnate the spread tow, covering it into a partially consolidated prepreg: 12 K carbon fiber spread tow/PP. Laminates were fabricated from the spread tow prepreg and control laminate composites were produced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Karl Meyer (China) Co., LTD [ 20 ] uses the conductivity of CF to provide heat by electrifying a CF bundle, thereby removing the sizing agent from the CF surface. Park et al [ 21 ] successfully achieved the expansion of 12 K carbon fiber from 7 mm to 20 mm by employing a self-designed tow spreading device under optimized process conditions. The mechanical widening method has the characteristics of simple device structure and low cost, but if the friction is too large, it is easy to damage the CF tow and reduce the mechanical properties of the prepreg prepared later.…”
Section: Introductionmentioning
confidence: 99%
“…Karl Meyer (China) Co., LTD [ 20 ] uses the conductivity of CF to provide heat by electrifying a CF bundle, thereby removing the sizing agent from the CF surface. Park et al [ 21 ] successfully achieved the expansion of 12 K carbon fiber from 7 mm to 20 mm by employing a self-designed tow spreading device under optimized process conditions. The mechanical widening method has the characteristics of simple device structure and low cost, but if the friction is too large, it is easy to damage the CF tow and reduce the mechanical properties of the prepreg prepared later.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, woven fabric using the spread tow can reduce the resin rich zone inside the composite material due to the thin tow thickness. Furthermore, studies have shown that applying the fabric to composite materials results in limiting cracks under fatigue load and improving fatigue life [25][26][27][28][29]. In terms of product value, carbon fiber spread tow can improve product value due to its beautiful appearance and can obtain various mechanical properties introduced above, therefore it is mainly used as a surface layer of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some high-end technologies are required to produce ultra-light and ultrathin fibre tow [3,4]. For carbon fibre bundles consisting tens of thousands of filaments (12k-48k), some methods have been developed to make a thin ply, such as mechanical spreading, ultrasonic spreading, airflow disturbing, electrostatic spreading [5,6], etc. The mechanical fibre spreading is the most used method in industry, and can achieve good effect of spreading by wrapping the fibre bundle through a series of pins.…”
Section: Introductionmentioning
confidence: 99%